Odpowiedzi

Najlepsza Odpowiedź!
  • Użytkownik Zadane
2009-05-26T18:02:51+02:00
(7-3)(3+7)= 49 - 9 = 40
(a-3)² - (a+4)(4-a) - 6(3-a)² = a² - 6a + 9 - (16 - a²) - 6(9 - 6a + a²) = a² - 6a + 9 - 16 + a² - 54 + 36a - 6a² = -4a² + 30a - 61
2009-05-26T18:03:50+02:00
(7-3)(3+7)= (7-3)(7+3) (można zmienić kolejność bo dodawanie jest przemienne) = 49 - 9 = 40
(a-3)²-(a+4(4-a)-6(3-a)² = a2 - 6a + 9 - (4+a)(4-a) - 6(9-6a+a2) =
= a2 - 6a + 9 - (16 - a2) - 54 + 36a - 6a2 = a2 - 6a + 9 -16 + a2 - 54 + 36a - 6a2 = -4a2 + 30a - 61
2009-05-26T18:06:44+02:00
(7-3)*(3+7)=4*10=40
a ten drugi to nie wiem
2009-05-26T18:17:43+02:00
(7-3)(3+7)=21+49-9-21=40

(a-3)²-(a+4)(4-a)-6(3-a)²= (a²-6a+9)-(a²+16)-6(9-6a+a²)=

=(a²-6a+9)-(a²+16)-54-36a+6a²= a²-6a+9-a²-16-54-36a+6a²=

=6a²-42a-61